Wall bound phenolics and total antioxidants in stored seeds of soybean (Glycine max) genotypes - KUMAR, S P JEEVAN; KUMAR, ASHUTOSH; V, RAMESH K; SINGH, CHANDU; AGARWAL, DINESH K; PAL, GOVIND; KUCHLAN, MRINAL K; SINGH, RAJIV (The Indian Journal of Agricultural Sciences, 2020)
Quality seed is the most important input for sustainable agricultural productivity. Recent studies highlight the role of antioxidants in scavenging the reactive oxygen species, which is an indicator for quality seed. In natural ageing conditions, reactive oxygen species accumulates in the seeds that lead to seed deterioration. Wall bound phenolics in seed coat are potential antioxidants that encounter the reactive oxygen species. Four soybean genotypes with different seed coat wall bound phenolics were studied in 2018 at ICAR-Indian Institute of Seed Science and found that the black coat seed such as kalitur and JS76-205 showed highest phenolic content (117.00 and 128.50 μg/mL) and antioxidant activity of 51.38 and 46.07 μg eq. ascorbic acid, respectively. On contrary, the harasoya (green coated seed) resulted lowest phenolic content 14.30 μg/mL, while in RAUS-05 (white coated seed) the antioxidant activity is 2.58 μg eq. ascorbic acid, which is significantly lower than the other genotypes. Further, the genotypes were evaluated for the seed quality parameters and observed that kalitur and JS76-205 showed higher germination percentage (80%) and vigor indices I (900.33) and II (35.01) than the other genotypes. These results substantiate the hypothesis that the seed coat wall bound phenolics with antioxidant properties could alleviate the reactive oxygen species, protects from mechanical and chemical damage and helps in enhancement of seed quality parameters.